Statistical evaluation of traffic survey data to relate peak hour volume to daily traffic volume / Mohd Helmizam Kamaruddin - Kamaruddin, Mohd Helmizam (Faculty of Civil Engineering, 2006)
In general, traffic volume studies are conducted to determine the number, movements, and classifications of roadway vehicles at a given location. There is a lot of useful information that we can obtained from the traffic volume data. One of the important elements in traffic volume measurement is peak volume studies since it is generally used for design and operational analysis. Statistical evaluation of traffic survey data is analyzed in this research to relate peak hour volume to daily traffic volume. Through this research, the studies are focused on peak hour volume data to determine whether it is related to daily traffic volume data in some way. In other words, data from peak hour volume will be studied and analyzed ascertain if daily traffic volume can be estimated with acceptable accuracy. From the research, it can be concluded that peak hour volume is related to daily traffic volume. The regression value R² = 0.9447 is obtained through the relationship between peak hour volume and daily traffic volume. By using linear equation y = 0.11x - 7.6343 the expected traffic volume is calculated. Then, Chi-Squared Distribution is used to check the accuracy of linear equation y = 0.11x - 7.6343 in calculating expected daily traffic volume. Based on Chi-Squared Distribution, there is a strong evidence to prove that there is relationship between peak hour volume and daily traffic volume. The percentages of error by using linear equation y = 0.11x - 7.6343 to calculate expected daily traffic is varies from 1.2 to 21.7%.However, for future application further research must be conducted to modify the linear equation y = 0.11x - 7.6343 in order to reduce the percentages of error in calculating expected daily traffic volume.